1994
DOI: 10.1159/000236802
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Major Brown Shrimp <i>(Penaeus aztecus)</i> Allergen as the Muscle Protein Tropomyosin

Abstract: Shrimp, a major seafood allergen, was investigated as a model food allergen. Extracts from both shrimp (Penaeus aztecus) meat and cooking fluid contain a substantial and similar amount of allergenic activity. A 36-kD allergen, demonstrated in both extracts by SDS-PAGE/Western blot analysis, reacted with 28/34 (82%) sera from shrimp-sensitive, skin test and RAST-positive, individuals. This allergen, named Pen a I, was isolated by SDS-PAGE; its amino acid composition was rich in aspartic and glutamic acids. A 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
1
8

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(160 citation statements)
references
References 6 publications
4
144
1
8
Order By: Relevance
“…All subjects had a history of respiratory (wheezing and shortness of breath), dermatologic (urticaria and angioedema), and/or gastrointestinal (nausea, vomiting, and diarrhea) symptoms occurring within 1 h after ingestion of shrimp, positive immediate skin prick test (wheal Ͼ3 mm) to brown shrimp extract, elevated shrimp-specific IgE by radioallergosorbent test (binding, Ͼ3%) (24,25), and strong IgE reactivity to purified shrimp tropomyosin by immunoblot analysis (1). For the mediator release experiments, additional sera (n ϭ 4) from shrimp-allergic subjects that had not been used for epitope characterization were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All subjects had a history of respiratory (wheezing and shortness of breath), dermatologic (urticaria and angioedema), and/or gastrointestinal (nausea, vomiting, and diarrhea) symptoms occurring within 1 h after ingestion of shrimp, positive immediate skin prick test (wheal Ͼ3 mm) to brown shrimp extract, elevated shrimp-specific IgE by radioallergosorbent test (binding, Ͼ3%) (24,25), and strong IgE reactivity to purified shrimp tropomyosin by immunoblot analysis (1). For the mediator release experiments, additional sera (n ϭ 4) from shrimp-allergic subjects that had not been used for epitope characterization were included.…”
Section: Methodsmentioning
confidence: 99%
“…Pen a 1, the tropomyosin of brown shrimp, Penaeus aztecus, is the only major allergen of this particular shrimp species and is recognized in Ͼ80% of shrimp-allergic subjects (1). Pen a 1 inhibited at least 75% of patients' IgE radioallergosorbent test reactivity to whole body shrimp extract, indicating that Pen a 1 is also responsible for most of the allergenic activity of shrimp (2).…”
mentioning
confidence: 99%
“…The allergen in shrimp is tropomyosin, a heat-stable coiled-coil protein with a molecular weight of between 34 and 38 kDa (Daul et al, 1994;Shanti et al, 1993;Jeoung et al, 1997;Leung et al,1996;Motoyama et al, 2006). It was previously found that in an aqueous extract of shrimp protein, tropomyosin was adsorbed at higher levels onto stainless steel surfaces than other proteins in the extract (Thammathongchat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…So far, allergens of 34 to 38 kDa identified as tropomyosin have been established as the major allergens of a number of prawn, termed Pen i 1 [6] , Pen a 1 [7] and Met e 1 [8] depending on the species used. In addition, tropomyosin has also been identified as the major allergen of other crustaceans [9,10] , mollusks [11][12][13][14][15] , house dust mites [16,17] and cockroaches [18,19] .…”
Section: Introductionmentioning
confidence: 99%